The prevalence, profile, and prognosis of heart failure with preserved ejection fraction: A South African tertiary hospital experience - Nshuti, Shema David (Department of Medicine, 2023)
Background. There is limited data on heart failure with preserved ejection fraction (HFpEF) in Sub-Saharan Africa. We therefore aimed to describe the prevalence, profile and outcomes of HFpEF patients admitted to a South African tertiary hospital. Methods. We retrospectively reviewed all consecutive de novo heart failure admissions to Groote Schuur Hospital in Cape Town between January 2016 and December 2017. The socio-demographic profile, clinical characteristics and outcomes were analysed. Poor outcome was defined as death or readmission to hospital within the first twelve months after the index diagnosis. Results. Of the 315 admissions for de novo acute heart failure, 42 patients (13.3%) had HFpEF. This female preponderant (81.0%) cohort had a median age of 55.5 years (interquartile range (IQR) 47-66 years). Hypertension (85.7%), chronic kidney disease (CKD) (40.5%) and diabetes (40.5%) were common comorbidities. The most frequent electrocardiographic (ECG) abnormalities included abnormal T wave inversion (38.1%), left ventricular hypertrophy (LVH) (16.7%) and left bundle branch block (LBBB) (11.9%). Atrial fibrillation (2.4%) and atrial flutter (2.4%) were uncommon. The main echocardiographic abnormalities were concentric LVH (81.0%), left atrial enlargement (45.2%) and evidence of diastolic dysfunction (92.9%). Within the first year after diagnosis, 35.7% of patients were readmitted to hospital for heart failure and 11.9% died. Conclusion. The prevalence of HFpEF in our population was much lower than what has been reported elsewhere. In this cohort, HFpEF predominantly affected middle-aged females with hypertension, diabetes and CKD. Almost half of the cohort (47.6%) had a poor outcome within the first year after diagnosis.